Mathematical reserves vs longevity risk in life insurances - Homa, Magdalena (Ryzyko długowieczności a wymagany poziom rezerw w ubezpieczeniach na życie i dożycie, 2020)
Insurers wanting to provide protection against unforeseen losses should establish an appropriate level of reserves, which should balance the risk borne by the insurer so as to guarantee the financial security of the insured. The system including the financing requirements tailored to the real risks is called the Solvency II. According to that the valuation of classic life insurance should consider the real risk, which includes risk of death and the change in value of money over time. This method of calculating reserves does not ensure the protection of collected funds by aggregation and the individual risk of longevity, which may negatively affect the long-term financial stability of insurers as well as the level of financial security for the insured. Therefore, the aim of this paper is to modify the calculation methods and, above all, to correct reserves within the period of insurance, taking into account the current expectation of the future projected length
Econometrics = Ekonometria, 2020, Vol. 24, No. 1, s. 23-38
Keywords: longevity risk; Solvency II; required mathematical reserves; ryzyko długowieczności; wymagany poziom rezerw matematycznych